Гапнинг синтактик таҳлилига ёндашувлар (FAN va JAMIYAT, 2016)
The article deals with the different approaches to syntactic analysis of sentences in world linguistics, and the issues demanding the discussion, such as the analysis of sentences according to components and syntaxemes. The analysis of the structure of sentences distributing them in compo- nents in the functional syntax demands separate units of the analysis distributing them into syntaxemes participating in the sentence structure.